Ratio analysis of financial statements for performance assessment - Nurhalija; Alimuddin (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study aims to analyse financial statements to assess the financial performance and identify the years in which PT Indofood Sukses Makmur Tbk and PT Mayora Indah Tbk demonstrated strong performance. The research was conducted by analysing annual financial reports, and the research type used is descriptive analysis. The data used is secondary data, namely data obtained from company records and presented as period financial reports. Furthermore, the author's data analysis technique uses financial ratio analysis tools on the data. The overall research results of PT Indofood Sukses Makmur Tbk and PT Mayora Indah Tbk for the period 2021-2022 are considered good because the company shows that its current assets exceed its current liabilities so that the company has no difficulty in paying off its current liabilities. The companies PT Indofood Sukses Makmur Tbk and PT Mayora Indah Tbk generate profits quite well, where the company's total invested assets continue to increase so that the company shows improvement.